A systematic analysis of genetic dilated cardiomyopathy reveals numerous ubiquitously expressed and muscle‐specific genes. (2nd March 2015) - Harakalova, Magdalena; Kummeling, Gijs; Sammani, Arjan; Linschoten, Marijke; Baas, Annette F.; van der Smagt, Jasper; Doevendans, Pieter A.; van Tintelen, J. Peter; Dooijes, Dennis; Mokry, Michal; Asselbergs, Folkert W.
Abstract : Aims: Despite considerable progress being made in genetic diagnostics for dilated cardiomyopathy (DCM) using panels of the most prevalent genes, the cause remains unsolved in a substantial percentage of patients. We hypothesize that several previously described DCM genes with low or unknown prevalence have been neglected, which, if catalogued, could increase the yield of diagnostic DCM testing. The aim of this study is to catalogue all genetic evidence on DCM comprehensively. Methods and results: We have conducted a systematic literature search on PubMed, Embase, and OMIM to find genes implicated in syndromic and non‐syndromic DCM and peripartum cardiomyopathy (PPCM). Our search yielded 110 nuclear protein‐coding genes and 24 mitochondrial DNA genes. For nuclear genes, in addition to 42 genes sufficiently reviewed previously (group A), we provide a comprehensive annotation of the level of genetic evidence for the remaining 68 genes (group B). Next, we investigated the tissue specificity of the collected genes using public RNA sequencing data. We show that genes primarily expressed in heart and skeletal muscle are more likely to result in DCM with possible skeletal myopathies, while genes expressed ubiquitously cause DCM with extramuscular manifestations. Conclusion: This comprehensive analysis of DCM‐associated genes revealed a much higher number of genes than currently screened in diagnostics. Since most genes in group B have only been found mutated in single DCM patients or families, their importance for DCM genetic diagnostics needs to be validated in large cohorts. Targeted sequencing of validated DCM‐implicated protein‐coding genes and mitochondrial DNA, together with consideration of the tissue specificity of mutated genes, may facilitate further genotype–phenotype studies in DCM.